2016
DOI: 10.1080/08927014.2016.1191068
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica isolates from layer farm environments are able to form biofilm on eggshell surfaces

Abstract: This study examined the eggshell biofilm forming ability of Salmonella enterica isolates recovered from egg farms. Multicellular behaviour and biofilm production were examined at 22 and 37°C by Congo red morphology and the crystal violet staining assay. The results indicated that the biofilm forming behaviour of Salmonella isolates was dependent on temperature and associated with serovars. Significantly greater biofilm production was observed at 22°C compared with 37°C. The number of viable biofilm cells attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
17
0
4
Order By: Relevance
“…Horizontal contamination occurs when an egg contacts a contaminated environment ( Gantois et al, 2009 ). Bacteria can then adhere to the surface of the egg and migrate into eggshell pores ( Gantois et al, 2009 ) or form biofilms on the shell surface ( Pande et al, 2016b ) representing a risk for downstream contamination of food items. In Australia, S. Enteritidis is not endemic on commercial poultry farms ( OzFoodNet Working Group, 2015 ), thus, S. Typhimurium contamination of the layer hen farm environment represents an important public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal contamination occurs when an egg contacts a contaminated environment ( Gantois et al, 2009 ). Bacteria can then adhere to the surface of the egg and migrate into eggshell pores ( Gantois et al, 2009 ) or form biofilms on the shell surface ( Pande et al, 2016b ) representing a risk for downstream contamination of food items. In Australia, S. Enteritidis is not endemic on commercial poultry farms ( OzFoodNet Working Group, 2015 ), thus, S. Typhimurium contamination of the layer hen farm environment represents an important public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) is based on surface scattering and absorption of electrons achieving high depth yielding a 3-D appearance, and allows the visualization special of the biofilm and to know the distribution of bacteria and EPS dispersed on biofilms (Clayborn, Adams, Baker, & Ricke, 2015). SEM has been used to study the ability of bacteria to develop biofilms on different substrates and several environmental conditions (Pande, McWhorter, & Chousalkar, 2016;De Oliveira et al, 2014). It allows the quantification of area, volume and thickness of the biofilm (Azeredo et al 2017) with a high resolution (50 to 100 nm) and depth of field with a wide range of magnifications (20 to 30000 X).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The relative expression of genes involved on curli, fimbriae and cellulose production (csgD, csgB, adrA and bapA) has permitted to detected biofilm formation by Salmonella on eggshells (Pande, McWhorter, & Chousalkar, 2016). However, expression of these gens and subsequent biofilm formation is influenced by growth media, indicating a strong dependence of environmental conditions on biofilm formation (Wang, Dong, Wang, Xu, & Zhou, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A major problem related to this pathogen is that Salmonella normally causes asymptomatic intestinal infections in birds over 2 months, facilitating the spread of this pathogen among flocks. In this sense, Pande et al . demonstrated that Salmonella strains isolated from egg farms and belonging to different serotypes were able to form biofilms on eggshell surfaces under different temperature conditions.…”
Section: Livestock and Produce Farmsmentioning
confidence: 99%